Antimicrobial activity of Bacillus paramycoides from Xiem duck against poultry pathogens - NGUYEN PHUONG THUY; NGUYEN THANH TUU (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Thuy NP, Tuu NT. 2025. Antimicrobial activity of Bacillus paramycoides from Xiem duck against poultry pathogens. Biodiversitas 26: 5567-5573. Antimicrobial Resistance (AMR) in poultry production poses a significant threat, demanding the development of effective antibiotic alternatives. This study aimed to isolate and identify native Bacillus strains from the gastrointestinal tract of Vietnamese Xiem ducks (Cairina moschata) and screen them for antagonistic activity against key poultry pathogens. Using heat-shock isolation and agar well diffusion assays, 30 different Bacillus species were obtained from 50 healthy ducks. In vitro screening via an agar well diffusion assay showed that over 93% of these isolates possessed broad-spectrum antagonistic activity against Escherichia coli, Salmonella enterica, and Staphylococcus aureus. Among 30, isolate B10 exhibited the highest efficacy, creating significant inhibition zones against E. coli (?10 mm), S. enterica (6-9 mm), and S. aureus (6-9 mm). Molecular analysis of the 16S rRNA gene identified isolate B10 as Bacillus paramycoides. This study reports the first identification of B. paramycoides from Xiem ducks, highlighting the importance of indigenous poultry as a reservoir for novel, host-derived probiotics. However, given its taxonomic affiliation with the B. cereus group, a rigorous safety evaluation, including genomic screening for virulence factors, is an essential prerequisite for its future development and application in sustainable poultry farming.